2002
DOI: 10.1016/s0022-5347(05)65393-1
|View full text |Cite
|
Sign up to set email alerts
|

NEOADJUVANT ANDROGEN ABLATION BEFORE RADICAL PROSTATECTOMY IN cT2bNxMo PROSTATE CANCER: 5-YEAR RESULTS

Abstract: Although 3 months of androgen deprivation before radical prostatectomy resulted in an apparently significant decrease in positive surgical margins, a 5-year followup does not indicate any difference in the recurrence rate. Until studies document improvement in biochemical or clinical recurrence with longer periods of treatment, induction androgen deprivation before radical prostatectomy is not indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
143
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(164 citation statements)
references
References 12 publications
10
143
1
4
Order By: Relevance
“…A phase III study of NAD before surgery for T2b cancer patients was reported by Soloway et al 33 No benefit was seen for the use of AD in terms of BF rates; however, for margin-negative prostate cancer BF rates were higher with than without NAD. As BF was still seen in negative margin cases, it is potentially possible that prostate cancer cells migrated outside the prostate before the surgical procedure.…”
Section: Androgen Deprivation and Radiation Therapymentioning
confidence: 98%
“…A phase III study of NAD before surgery for T2b cancer patients was reported by Soloway et al 33 No benefit was seen for the use of AD in terms of BF rates; however, for margin-negative prostate cancer BF rates were higher with than without NAD. As BF was still seen in negative margin cases, it is potentially possible that prostate cancer cells migrated outside the prostate before the surgical procedure.…”
Section: Androgen Deprivation and Radiation Therapymentioning
confidence: 98%
“…3 Neoadjuvant ADT before RP decreases the positive surgical margin rate but has not been confirmed to improve relapse rates or survival. 4 Among intermediate and high risk patients receiving brachytherapy, the addition of ADT might improve relapse rates, but not survival. 5 Combination EBRT with standard BT does not consistently improve biochemical relapse rates compared to BT alone.…”
mentioning
confidence: 99%
“…Thus far, however, trials testing the neoadjuvant use of androgen deprivation therapy (7,8) or early chemotherapy (9) in prostate cancer have been disappointing and have failed to show compelling clinical or survival advantages. Recently, docetaxel, either alone or in combination with estramustine, has shown an excellent biochemical response rate (significant prostate-specific antigen reductions in z50% of men; ref.…”
mentioning
confidence: 99%